English Learning Strategies Analysis among Senior High School Students in Sleman Regency, Yogyakarta, Indonesia - Mochammad Choirul Anam; Ima Widyastuti; Victa Sari Dwi Kurniati; Lalarin Tongchai (Universitas Sarjanawiyata Tamansiswa, 2025)
English is a crucial subject in Indonesia, with students studying it from junior high school to university levels. Poor English proficiency is attributed to the long time spent in the classroom. This study aims to analyze English language learning strategies used by senior high school students in Indonesia, focusing on metacognitive methods and their impact on teaching and learning outcomes. Using the SILL version 7.0 questionnaire, the current study attempts to examine the English learning strategies among 109 students of senior high school in Yogyakarta, Indonesia. The data were collected via Google Form. The spreadsheet result of the participants’ input was analyzed under the SILL version 7.0 language learning strategies level. The study indicates that the Cognitive strategies are the most frequent used by the participants in the present study.